Avaliação de toxicidade por dose única e doses repetidas de formulações de dentifrícios fluoretados contendo óleo essencial de Lippia sidoides cham - Lima, Mateus Ramos Plutarco (2022)
The development of new products with antimicrobial properties has gained more and more marketing space, due to the emergence of microorganisms resistant to currently available drugs. In this scenario, the association of essential oils to oral hygiene products that are derived from plants and detain antimicrobial properties appears as a promising alternative for the development of new products in the control of dental caries, as well as in the control of periodontal disease and other biofilm-dependent oral infections. Toothpastes are cosmetic products commonly used for daily oral hygiene. Before being made available for commercial purposes and human consumption, safety tests are warranted to evaluate their toxicity. The present study aimed to evaluate the toxicity of single and repeated doses of diluted formulations of fluoride toothpastes containing essential oil of Lippia sidoides Cham. (OELS-500: 1% oil of Lippia sidoides (OELS), 500 ppm of fluorine, sodium lauryl sulfate (LSS) as surfactant and xylitol as sweetener; OELS-1000: 1% OELS, 1000 ppm of Fluorine, LSS and erythritol; 1.5OELS-500: 1.5% OELS, 500 ppm of Fluoride, LSS and erythritol) in Wistar rats of both sexes. The toxicity of toothpastes was evaluated in single (acute phase) and repeated doses, during an observation period of 28 days (subchronic phase), according to protocols numbers 423 and 407 established by the Organization for Economic Co-operation and Development (OECD), respectively. After the tests, all animals were submitted to autopsy for histological analysis, biochemical serum dosages, in addition to leukogram and body mass variation. As a result, we observed that in the single dose phase, the 1.5OELS-500 dentifrice formulation presented the best toxicity results related to biochemical parameters, when compared to the naïve group. This formulation was selected for the repeated dose phase. In the subchronic phase, no significant differences in biochemical analysis were observed between the test, control and naïve groups. These results suggest the safety of these formulations in the analysed phases of the study, since in addition to not having observed animal deaths during the experimental phase, most of the analysis did not show any change in the biological parameters between the test groups and the control group. However, further safety studies are needed to evaluate the formulations before starting clinical trials in humans.